Experimental and Numerical Investigation of Grain Refinement in Low Carbon Steel Sheets During Constrained Groove Pressing - Nejati, Faeze; Sojoodi, Soheila (Mechanical Technology and Engineering Insights, 2024)
In the current research work, an Ultrafine-Grained (UFG) microstructure was fabricated in low-carbon steel sheets using the Constrained Groove Pressing (CGP) technique, a state-of-the-art method for producing small grain sizes via Severe Plastic Deformation (SPD). The dies for the CGP were designed and fabricated taking into account the principles of CGP (groove angle of 45° and groove width and depth equal to the sheet thickness, 2 mm). A finite element analysis was performed in 2D plane-strain mode using ABAQUS to examine the distribution of effective plastic strain. Sheets of low-carbon steel measuring 102×50×2 mm³ underwent up to four CGP passes. Properties such as hardness and tensile strength were assessed using the Vickers hardness test and the tensile test (as per the guidelines of ASTM E8M). Optical microscopy was performed to analyze the microstructural evolution in accordance with ASTM standards E03-1, E407-99, and E112. The simulation results showed that, on average, an effective strain of approximately 1.15 per pass can be achieved. Grain diameter was found to decrease from 22.5 µm (ASTM grain size number 8) in the as-received state to 4.5 µm (ASTM number 13.5) after four passes, with an 80% reduction. The increase in hardness was observed to range from 52 HV to 252 HV, representing a 385% improvement. It was proved that the Hall-Petch relation holds with the linear fit (R² > 0.98). This shows that grain refinement is the major strengthening parameter. From both experimental and FEA results, it can be concluded that the CGP process is highly efficient for obtaining ultra-fine-grained sheets with improved mechanical properties.